The Dependence of the Out Put Power and Absorptivity of Waveguides and Nano Solar Cells on the low Frequency and Dimensions - M. Widaa’, Einas; D. Abdalla, Mubarak (Gezira Journal of Engineering and Applied Sciences, 2021)
One of the most prominent problems facing Scientists in designing solar cells nowadays is to design highly efficient solar cells by increasing its light absorptivity. This needs a design of highly efficient solar cells having nanometer dimensions in a form of a waveguide.      Since the design of such cells is difficult in the Sudan, this paper attempted to design absorption microwave cells to know how the absorption depends on the dimensions of the rectangular waveguide